SIMULASI PEMBAKARAN SERBUK BIOMASSA SEKAM PADI PADA PROSES GASIFIKASI BERBASIS SOLAR CELL DENGAN VARIASI JUMLAH GLOWPLUG PADA PIPA: SIMULASI PEMBAKARAN SERBUK BIOMASSA SEKAM PADI PADA PROSES GASIFIKASI BERBASIS SOLAR CELL DENGAN VARIASI JUMLAH GLOWPLUG PADA PIPA - suli, suliono (Jurnal Teknik Juara Aktif Global Optimis, 2021)
Gasification is the process of converting solid biomass into a combustible gas. The process is carried out in a reactor known as a gasifier. The gasification process which is modeled in the simulation in this soliworks flow simulation software includes combustion pipes, reactors, and syn-gas pipes. The fuel used is rice husk powder with a capacity of 10.15 kg with top 57 cm bottom 54 cm with a height of 60 cm. This study uses several variations of glowplug in the combustion pipe with an average glowplug unit temperature of 797.80 °C. The air will be exhaled by a blower with a speed of 2924 rpm. Until the incoming air rate passes through the gasification reactor and the gas shape is displayed in a contour simulation which has a length of 102.98 mm. Inside the gasifier reactor, the upper reactor temperature is 474.25 °C, the middle reactor is 330.55 °C, and the bottom reactor is 394.40 °C. While the pipe that has a glowplug gets an air speed of 5.54 m/s and a temperature of 67.74 °C. Keywords: Gasification, Gasifier Reactor, Solidwork, Simulation, Flow Simulation, and Glowplug